2021
DOI: 10.2298/tsci200729338e
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of thermal stresses generated in laminated composite structure exposed to low temperatures

Abstract: This paper presents numerical calculation of thermal stresses generated in a carbon fiber-epoxy laminated composite structure which is operating at low temperatures. The thermal stress evaluation is based on the finite element method. A sample problem involving generated thermal stresses in a real laminated composite structure, exposed to low temperatures (four different temperature levels), is analyzed and discussed. Obtained results suggest that these thermal stresses remarkably decrease th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Moreover, studies have also been conducted to study the time-temperature creep behavior on CFRP, [23][24][25] while other researchers investigated the numerical simulation of the thermal stress of the CFRP laminated composites. [26][27][28] However, Benli et al 29 showed that the contribution of thermal stress to impact damage increases with decreasing temperature. The stress at low temperatures significantly influences the impact damage and parameters of unidirectional CFRP composite laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have also been conducted to study the time-temperature creep behavior on CFRP, [23][24][25] while other researchers investigated the numerical simulation of the thermal stress of the CFRP laminated composites. [26][27][28] However, Benli et al 29 showed that the contribution of thermal stress to impact damage increases with decreasing temperature. The stress at low temperatures significantly influences the impact damage and parameters of unidirectional CFRP composite laminates.…”
Section: Introductionmentioning
confidence: 99%